Abortion and the Equality of Reasons - Imber, Jonathan B. (The Hastings Center report, 1980)
Book reviewed in this article: A Private Choice: Abortion in America in the Seventies. By John T. Noonan, Jr. Aborting America. By Bernard N. Nathanson, M.D., with Richard N. Ostling.